CONTRIBUTION OF INDONESIAN NATIONAL STANDARD (SNI) ON GROSS DOMESTIC PRODUCTS (GDP) - BIATNA DULBERT TAMPUBOLON; FEBRIAN ISHARYADI; UTARI AYUNINGTYAS; ARY BUDI MULYONO; MEILINDA AYUNDYAHRINI; HERMAWAN FEBRIANSYAH; AJUN TRI SETYOKO; REZA LUKIAWAN; PUTTY ANGGRAENI; Ellia Kristiningrum; DANAR AGUS SUSANTO; ENDI HARI PURWANTO; Teguh Adinugroho; Novin Aliyah (JURNAL STANDARDISASI, 2023)
Gross Domestic Product (GDP) is the number of goods and services produced by a country in a certain period as a measuring tool for a country's economic development. GDP comprises many factors, including national household consumption, investment, state consumption, exports, and imports. Standards are inherent in goods and services produced, consumed, and nationally and internationally traded. This study aims to determine the effect of standards on GDP. The method used is econometrics through case studies in Indonesia by considering the independent factors, namely fixed capital, number of workers, patents, and Indonesian National Standard (SNI), while the dependent factor is GDP. The results showed that a 1% percent increase in  SNI, patents, fixed capital, and labor could increase Indonesia's GDP by 0.3%, 0.08%, 0.04%, and 0.4 %, with alpha 5% from 1998 to 2017, respectively. With an average SNI growth of 5.43%, the contribution of SNI is 1.63% year to the average GDP growth. In monetary terms, a 1% increase in total SNI in 2017 increased to about 5.9 trillion in GDP.